A CEACAM6-High Airway Neutrophil Phenotype and CEACAM6-High Epithelial Cells Are Features of Severe Asthma - Shikotra, Aarti; Choy, David F; Siddiqui, Salman; Arthur, Greer; Nagarkar, Deepti R; Jia, Guiquan; Wright, Adam K A; Ohri, Chandra M; Doran, Emma; Butler, Claire A; Hargadon, Beverley; Abbas, Alexander R; et al. (The Journal of immunology (1950), 2017)
Severe asthma represents a major unmet clinical need; understanding the pathophysiology is essential for the development of new therapies. Using microarray analysis, we previously found three immunological clusters in asthma: Th2-high, Th17-high, and Th2/17-low. Although new therapies are emerging for Th2-high disease, identifying molecular pathways in Th2-low disease remains an important goal. Further interrogation of our previously described microarray dataset revealed upregulation of gene expression for carcinoembryonic Ag cell adhesion molecule (CEACAM) family members in the bronchi of patients with severe asthma. Our aim was therefore to explore the distribution and cellular localization of CEACAM6 using immunohistochemistry on bronchial biopsy tissue obtained from patients with mild-to-severe asthma and healthy control subjects. Human bronchial epithelial cells were used to investigate cytokine and corticosteroid in vitro regulation of CEACAM6 gene expression. CEACAM6 protein expression in bronchial biopsies was increased in airway epithelial cells and lamina propria inflammatory cells in severe asthma compared with healthy control subjects. CEACAM6 in the lamina propria was localized to neutrophils predominantly. Neutrophil density in the bronchial mucosa was similar across health and the spectrum of asthma severity, but the percentage of neutrophils expressing CEACAM6 was significantly increased in severe asthma, suggesting the presence of an altered neutrophil phenotype. CEACAM6 gene expression in cultured epithelial cells was upregulated by wounding and neutrophil elastase. In summary, CEACAM6 expression is increased in severe asthma and primarily associated with airway epithelial cells and tissue neutrophils. CEACAM6 may contribute to the pathology of treatment-resistant asthma via neutrophil and airway epithelial cell–dependent pathways.